ÐšÑ€Ð¸Ð¾ÐºÐ¾Ð½ÑÐµÑ€Ð²Ð¸Ñ€Ð¾Ð²Ð°Ð½Ð½Ñ‹Ð¹ Ð°Ð»Ð»Ð¾Ð³ÐµÐ½Ð½Ñ‹Ð¹ ÐºÐ¾ÑÑ‚Ð½Ñ‹Ð¹ Ð¼Ð¾Ð·Ð³ â€“ Ð½Ð¾Ð²Ð°Ñ Ð¼Ð¸ÑˆÐµÐ½ÑŒ Ð¸Ð¼Ð¼ÑƒÐ½Ð¾Ð¼Ð¾Ð´ÑƒÐ»Ð¸Ñ€ÑƒÑŽÑ‰ÐµÐ¹ Ð°ÐºÑ‚Ð¸Ð²Ð½Ð¾ÑÑ‚Ð¸ ÐºÐ»ÐµÑ‚Ð¾Ðº Ñ„ÐµÑ‚Ð°Ð»ÑŒÐ½Ð¾Ð¹ Ð¿ÐµÑ‡ÐµÐ½Ð¸ - Goltsev, A. N.; Ostankova, L. V.; Matsevitaya, I. Yu.; Dubrava, T. G. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2008)
Modulating activity of fetal liver cells at co-transplantation with cryopreserved allogeneic bone marrow was experimentally proved. This co-transplantation increases hemopoietic potential of allogeneic bone marrow and reduces its immune reactivity, manifesting in the activity of â€œgraft versus hostâ€ reaction and rise in the survival of recipients.